Tumor NLRP3-Derived IL-1β Drives the IL-6/STAT3 Axis Resulting in Sustained MDSC-Mediated Immunosuppression - Tengesdal, Isak W.; Dinarello, Alberto; Powers, Nicholas E.; Burchill, Matthew A.; Joosten, Leo A. B.; Marchetti, Carlo; Dinarello, Charles A. (Frontiers in Immunology, 2021)
Tumors evade the immune system by inducing inflammation. In melanoma, tumor-derived IL-1β drives inflammation and the expansion of highly immunosuppressive myeloid-derived suppressor cells (MDSCs). Similar in many tumors, melanoma is also linked to the downstream IL‐6/STAT3 axis. In this study, we observed that both recombinant and tumor-derived IL-1β specifically induce pSTAT3(Y705), creating a tumor-autoinflammatory loop, which amplifies IL-6 signaling in the human melanoma cell line 1205Lu. To disrupt IL-1β/IL-6/STAT3 axis, we suppressed IL-1β-mediated inflammation by inhibiting the NOD-like receptor protein 3 (NLRP3) using OLT1177, a safe-in-humans specific NLRP3 oral inhibitor. In vivo, using B16F10 melanoma, OLT1177 effectively reduced tumor progression (p< 0.01); in primary tumors, OLT1177 decreased pSTAT3(Y705) by 82% (p<0.01) and II6 expression by 53% (p<0.05). Disruption of tumor-derived NLRP3, either pharmacologically or genetically, reduced STAT3 signaling in bone marrow cells. In PMN-MDSCs isolated from tumor-bearing mice treated with OLT1177, we observed significant reductions in immunosuppressive genes such as Pdcd1l1, Arg1, Il10 and Tgfb1. In conclusion, the data presented here show that the inhibition of NLRP3 reduces IL-1β induction of pSTAT3(Y705) preventing expression of immunosuppressive genes as well as activity in PMN-MDSCs.